Effects of storage on brown rice (Oryza sativa L.) metabolites, analyzed using gas chromatography and mass spectrometry. Issue 6 (18th May 2020) - Wang, Changyuan; Feng, Yuchao; Zhang, Shu; Fu, Tianxin; Sheng, Yanan; Zhang, Yiwei; Jiang, Yingjun; Yu, Miao; Zhang, Liyuan; Zhang, Dongjie
Abstract: Metabolomic studies were carried out using gas chromatography and mass spectrometry (GC‐MS) on Daohuaxiang variety rice ( Oryza sativa L.) from the Wuchang Geographical Indication Rice Protection Area in Heilongjiang Province, to investigate the effects of storage on brown rice metabolism. The data were subjected to principal component analysis (PCA), orthogonal partial least squares‐discriminant analysis (OPLS‐DA), and cluster analysis using software such as SIMCA. Analysis of the samples led to the identification of a total of 160 metabolites. No significant differences were found in the amount of metabolites before and after storage. A total of 31 differential metabolites were screened, and the changes in metabolite content showed a "reverse change" overall. Storage significantly changed the content of various metabolites in rice, with fatty acids impacted most significantly. Metabolic pathway analysis revealed that fatty acid biosynthesis is a key metabolic pathway in rice storage. The degradation of brown rice quality caused by storage is closely related to the composition and content of its metabolites, and that change in lipid content significantly affects brown rice quality during storage. Abstract : Storage has a small effect on the amount of brown rice metabolites and a large effect on the composition of metabolites. Storage has a significant effect on the content of lipids and carbohydrates, and has a "reverse change" trend. Storage has the greatest impact on fatty acid synthesis pathways. Lauric acid is a key metabolite for lipid metabolism during storage of Daohuaxiang variety rice. Lipids are the main factors affecting brown rice quality during storage.